2020
DOI: 10.1038/s41598-020-72210-4
|View full text |Cite
|
Sign up to set email alerts
|

An inherent instability study using ab initio computational methods and experimental validation of Pb(SCN)2 based perovskites for solar cell applications

Abstract: Perovskite materials with ABX3 chemistries are promising candidates for photovoltaic applications, owing to their suitable optoelectronic properties. However, they are highly hydrophilic and unstable in nature, limiting the commercialization of perovskite photovoltaics. Mixed halide ion-doped perovskites are reported to be more stable compared to simple ABX3 chemistries. This paper describes ab initio modeling, synthesis, and characterization of thiocyanate doped lead iodide CH3NH3PbI(3−x)(SCN)x perovskites. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The absorption coefficient (α), which is directly proportional to the optical density and incident photon energy (hυ), can be used to determine the optical bandgap by extrapolating the straight-line portion of the plot of the quantity (αhυ) 2 vs. photon energy [22]. The authors of a previous study reported that the calculated bandgap of perovskite materials from the Tauc plot compares with the discrete Fourier transform computed bandgaps [23]. In addition, the bandgap can be estimated using the Tauc plot without considering the exciton binding energy, and the results were in good agreement with the energy levels (conduction/valence band) derived from the photoelectron spectroscopy measurement [24].…”
Section: Resultsmentioning
confidence: 99%
“…The absorption coefficient (α), which is directly proportional to the optical density and incident photon energy (hυ), can be used to determine the optical bandgap by extrapolating the straight-line portion of the plot of the quantity (αhυ) 2 vs. photon energy [22]. The authors of a previous study reported that the calculated bandgap of perovskite materials from the Tauc plot compares with the discrete Fourier transform computed bandgaps [23]. In addition, the bandgap can be estimated using the Tauc plot without considering the exciton binding energy, and the results were in good agreement with the energy levels (conduction/valence band) derived from the photoelectron spectroscopy measurement [24].…”
Section: Resultsmentioning
confidence: 99%
“…Lead halide perovskite nanocrystals (PeNCs) have become a promising candidate in the field of optoelectronics owing to their large optical absorption coefficient (10 4 –10 5 cm –1 ), tunable band gap, narrow emission bandwidth, and high photoluminescence quantum yield (PLQY). The power conversion efficiency (PCE) of the monolithic perovskite/silicon tandem solar cell has already reached 29.15% within a very short period . Meanwhile, multicolor light-emitting diodes (LEDs) and low threshold optical-pumped lasers have been realized with excellent performance. , However, the ionic nature of PeNCs results in a significant drawback of high environmental sensitivity, which limits their practical applications. , Furthermore, up to now, studies have shown that high-temperature, oxygen, moisture, ultraviolet (UV) light exposure, and structural transformation lead to the decomposition of perovskite materials and degrade the device stability. Therefore, progress in improving the stability of the material without sacrificing its performance is crucial for the development of PeNCs in the future.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 However, the ionic nature of PeNCs results in a significant drawback of high environmental sensitivity, which limits their practical applications. 9,10 Furthermore, up to now, studies have shown that high-temperature, oxygen, moisture, ultraviolet (UV) light exposure, and structural transformation lead to the decomposition of perovskite materials and degrade the device stability. 11−15 Therefore, progress in improving the stability of the material without sacrificing its performance is crucial for the development of PeNCs in the future.…”
Section: ■ Introductionmentioning
confidence: 99%
“…38 Some scholars have also compared the tauc map data of perovskite materials with the simulation results of band gap simulation by discrete Fourier transform, and the results are very consistent. 39,40 From the tauc plot results, it can be seen that with the increase of ligand concentration, the energy gap also increases. It is speculated that the increase of ligand inhibits the growth of quantum dots, affects its size, and causes the change of energy gap.…”
Section: Resultsmentioning
confidence: 99%